Synthesis and characterization of MWCNT incorporated N, S-rGO supported CdS photocatalyst for the dissociation of water to hydrogen by visible light - Alam, Zahoor; Verma, Bhawna; Sinha, A.S.K. (Elsevier Ltd, 2020)
In the present study, MWCNT-N,S-rGO supported CdS was synthesized at a higher temperature by the gas-solid reaction. Photoactivity was measured and compared with N, S-rGO supported CdS. Incorporation of MWCNT prevents the restacking of the graphene layer and provides the high surface area for the dispersion of CdS which result in increasing the photoactivity of catalyst. It also increases the electrical conductivity which reduces the charge transfer resistance. Catalysts were characterized by FTIR, XRD, XPS, Raman spectroscopy, BET surface area analyzer, TEM, HRTEM, UV–Vis spectroscopy, PL spectroscopy, electrochemical impedance spectroscopy (EIS) and Mott. Schottky analysis. The characterization results confirmed that incorporating MWCNT in N,S- rGO resulted in a higher rate of electron generation and also a higher rate of transfer of electrons to the solid-liquid interface and hence a higher activity.
Keywords: Chemical interaction; MWCNT; Restacking; Solar hydrogen